Design, synthesis and evaluation of the QD-DTC–bisbiotin nanobioconjugate as a potential optical-SPECT imaging agent. Issue 2 (5th December 2014) - Bag, Narmada; Mathur, Rashi; Singh, Sweta; Hussain, Firasat; Chauhan, Ram Prakash; Chuttani, Krishna; Mishra, Anil Kumar
Abstract : Biotinylated dithiocarbamate ligand modified quantum dots improve targeting while maintaining the photoluminescence for efficient imaging applications. Abstract : Biomedical applications of semiconductor quantum dots (QDs) are still limited due to the decrease in their photoluminescence (PL) after surface modification for target specificity and in vivo imaging. This is being taken care of by choosing ligands which can enhance the tumour specificity without affecting the optical properties of the core QDs. In this study we have synthesized a dithiocarbamate (DTC) derivatised bisbiotin ligand (DTC–bisbiotin) and then functionalized it covalently over the CdSe–ZnS quantum dot surface to produce the (QD-DTC–bisbiotin) nanobioconjugate. The influence of the size of the QD nanobioconjugate (10–15 nm) and optical properties are evaluated by TEM, UV-Vis and fluorescence spectroscopy and have been found to be favourable for diagnostic imaging studies. The synthesized nanobioconjugate was further studied for its in vivo biodistribution and pharmacokinetics through a pre-targeting approach. In vivo pharmacokinetics and biodistribution studies were performed by radiolabelling the QD nanobioconjugate with 99m Technetium ( 99mTc QD-DTC–bisbiotin). 99mTc QD-DTC–bisbiotin showed significantly higher tumour uptake (5% ID g −1 ) with better tumour retention, high tumour/normal organ contrast and enhanced pharmacokinetics as compared to the native DTC–bisbiotin ligand. This illustrates that although the bivalent effect of bisbiotin ligand is responsible for the tumour uptake, the Enhanced Permeable and Retention (EPR) effect due to the size of the QD nanobioconjugate plays a major role in the enhanced pharmacokinetics and biodistribution. The efficient binding of 99m Tc with the QD nanobioconjugate also highlights its use as "a SPECT-optical imaging agent".